Survey of Cereal Consumption Habits in the Community of Djougou, Benin - Moutawakilou, Mouhamed N. El-Hadji Alassane; Chabi-Sika, J. Kisito; Noumavo, Agossou Danien Pacôme; SINA OROU, S. M. ABDEL HAZIZ; DOSSOU, JOSEPH; BABA-MOUSSA, LAMINE SAÏD; BABA-MOUSSA, FARID A. KADER (My University, 2023)
The cereal group occupies a prominent place in the dietary habits of people in northern Benin and there is little recent information on cereal consumption. This study aims to assess the consumption, acquisition and supply of cereals to households in the community of Djougou. A semi-directive survey with KoBoCollect was conducted among 369 households to collect individual ce- real food consumption data. The survey data processed by statistical tools showed that the most consumed cereals are maize (95%, p = 0.887), millet (58%, p = 0.755), rice (55%, p = 0.753), sorghum (15%, p = 0.635), wheat (5%, p = 0.920) and fonio barely 5%. The most common mode of acquisition in Djougou is purchase (50%, p = 0.947) but donation is also observed (25%, p = 0.988) as well as production observed in 20.6% of households. Purchases are made from retailers in local markets (45%, p = 0.920) but also in streets and alleys (30%, p = 0.765). The most widely used preservation technique is dry- ing at room temperature (70%, p = 0.995). Households most often dry in the areas provided in the field (50%, p = 0.783) and at home (40%, p = 0.643). The preferred storage location is the kitchen (60%, p = 0.790). The bedroom (20%, 0.669) and the store (15%, 0.522) are the alternative places for storing cereals. In addition, the supply costs of cereals increased between 2020 and 2021. This vertiginous rise in prices is due, among other things, to the co- vid19 pandemic. The various data generated not only make it possible to have fresh data but also to invest them in the assessment of health risks for the achievement of a high level of protection of the health and life of consumers.
Keywords: Cereals; Survey; Consumption Data; Food Safety; Benin